Analisis Peran Guru Agama Islam dalam Pengembangan Pendidikan Agama Islam di SD Inpres Ende 16 - Arafat, Siti (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The method used is descriptive qualitative, through primary and secondary data sources, using observation, interviews and documentation as data collection techniques. The results of the research show that the role of teachers in developing the Islamic Religious Education of students at SD Inpres Ende 16 is, namely, the role of teachers as educators and instructors, as mentors, as leaders, implementers of evaluations and as managers of teaching and learning activities by providing good examples, habituation good behavior, enforcing discipline, providing motivation/encouragement, providing rewards, punishments and creating a religious atmosphere that influences the growth and development of students' thinking inside and outside the classroom. Meanwhile, the supporting and inhibiting factors experienced by teachers are dominant in external factors, namely the family environment, institutional environment, both formal and non-formal, and the students' social environment.